Impact of value relevance of accounting information on share price: A study of listed Banks in Sri Lanka - Sangeerthana, P.; Pamila, S. (University of Jaffna, 2020)
This study aims to examine the impact of value relevance of accounting information on the share price of listed banks in Sri Lanka throughout 2015-2019. The banks' share price was used as the dependent variable whilst the independent variables include Earning per share, Book value per share, Dividend per share,, and net operational cash flow per share. The study made use of secondary data gathered from annual reports of banks. Descriptive and inferential analyses were performed. Regression analysis confirmed a significant impact of value relevance of accounting information on the share price of listed banks in Sri Lanka. Correlation analysis revealed a significant positive relationship between Earning per share, Book value per share, Dividend per share, and the share price of the banks, while operational cash flow per share has an insignificant positive relationship. This study's findings will assist both potential and existing investors in making investment decisions in listed banks in Sri Lanka.
Keywords: listed banks; share price; value relevance of accounting information